2020
DOI: 10.1016/j.adolescence.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating identity at the intersection of family legacy and present time life conditions: A qualitative exploration of central issues connected to identity and belonging in the lives of children of refugees

Abstract: Introduction: Most studies on refugee populations are organized around trauma-related issues and focus on explanations of pathological factors. Few studies are anchored in general developmental psychology with the aim of exploring normal age-specific developmental tasks and how the special circumstances associated with forced migration can influence that development. Methods: Using an ecological and transactional understanding of developmental trajectories, this qualitative study explored issues connected to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Erikson explored nuances and variance in these developmental processes and how social, historical, and political contexts interact with personal development (Syed and Fish, 2018). Healthy identity implies, in this perspective, sense of temporal and contextual integration and identity can be understood as an integration of the numerous, possibly conflicting, and aspects of individual lives (Akhtar, 1995;Johansen and Varvin, 2020). In Erikson's eight developmental stages, development in each stage is dependent on how successful or unsuccessful the previous stages have been.…”
Section: Tasks To Solve: Erikson's Stagesmentioning
confidence: 99%
“…Erikson explored nuances and variance in these developmental processes and how social, historical, and political contexts interact with personal development (Syed and Fish, 2018). Healthy identity implies, in this perspective, sense of temporal and contextual integration and identity can be understood as an integration of the numerous, possibly conflicting, and aspects of individual lives (Akhtar, 1995;Johansen and Varvin, 2020). In Erikson's eight developmental stages, development in each stage is dependent on how successful or unsuccessful the previous stages have been.…”
Section: Tasks To Solve: Erikson's Stagesmentioning
confidence: 99%
“…Our impression from the qualitative interviews was that many of our informants struggled with relating socially to anyone outside the immediate family. A separate study of children in refugee families, including several children of participants in this study, showed that the children took much responsibility for parents' social function, including relations outside the family [68,69]. Among the adult participants in the present study, however, some appeared to become more socially confident after the benign experience of talking with their therapist, and when the pressure of their trauma-related and depressive ruminations decreased.…”
Section: Plos Onementioning
confidence: 46%